2012
DOI: 10.1017/s0958344012000055
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Assisted Language Learning in university EFL courses in Japan: developing attitudes and skills for self-regulated learning

Abstract: This paper reports a project in which researchers at universities in Japan explored the use of Mobile Assisted Language Learning (MALL) practices by developing a learning module intended to help improve students’ scores on the TOEIC Listening and Reading Tests. MALL practices are currently being developed at universities in Japan because almost all students have mobile phones, many of them have had informal learning experiences with mobile devices, and students are integrating the communication and information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 15 publications
3
83
1
Order By: Relevance
“…One recent study confirmed that the Mobile-Assisted Language Learning (MALL) approach can improve students' English skills, while refining their self-study behavior and enhancing self-efficacy (Kondo, Ishikawa, Smith, Sakamoto, Shimomura, & Wada, 2012). A survey of 75 Japanese students found that over two-thirds of the students would like to use mobile phones for language learning in either the short-or long-term (Stockwell, 2008).…”
Section: Mobile-assisted Language Learningmentioning
confidence: 99%
“…One recent study confirmed that the Mobile-Assisted Language Learning (MALL) approach can improve students' English skills, while refining their self-study behavior and enhancing self-efficacy (Kondo, Ishikawa, Smith, Sakamoto, Shimomura, & Wada, 2012). A survey of 75 Japanese students found that over two-thirds of the students would like to use mobile phones for language learning in either the short-or long-term (Stockwell, 2008).…”
Section: Mobile-assisted Language Learningmentioning
confidence: 99%
“…Technology-enhanced language learning practices can not only engage EFL students in self-regulated learning (Lai & Gu, 2011;Kondo et al, 2012), but also produce a positive impact on their self-efficacy (Henderson, Huang, Grant, & Henderson, 2012;Kissau, 2012;Wu & Yang, 2016). In web-based learning settings, students who can employ self-regulatory strategies became more challengeable and more confident in understanding course materials or participating in learning activities (Chang, 2005).…”
Section: Self-regulation Online Self-regulation and English Self-effmentioning
confidence: 99%
“…In addition, smart devices were linked to faster reading and self-regulated style of learning among students (Kondo, 2012).…”
Section: Smart Devices \ Social Media and Students' Attitudes Towardsmentioning
confidence: 99%